2019
DOI: 10.1039/c8ra10050k
|View full text |Cite
|
Sign up to set email alerts
|

Halide-free neodymium phosphate based catalyst for highly cis-1,4 selective polymerization of dienes

Abstract: [Nd(μ-DEP)3]x/TIBA stereospecifically polymerizes myrcene in a pseudo-living Ziegler–Natta like catalytic system despite the absence of a halide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A halide-free complex, in which Nd is coordinated with three bidentate diethylphosphate (DEP) ligands ([Nd(μ-DEP) 3 ] x and combined with Al i Bu 3 , was reported by Stefan et al to promote M polymerization at room temperature. [55] High cis-1,4 selectivity (� 95 %), M n = 13-48.5 kg mol À 1 , and relatively narrow Ð (1.8) were detected. Kinetics experiments demonstrated pseudo-living character of polymerization, confirmed by the successful synthesis, through sequential monomer addition, of block copolymer poly(M-b-I) (M n = 15.5 kg mol À 1 , Ð = 3.1).…”
Section: Group 3 and Rare-earth Metalsmentioning
confidence: 96%
“…A halide-free complex, in which Nd is coordinated with three bidentate diethylphosphate (DEP) ligands ([Nd(μ-DEP) 3 ] x and combined with Al i Bu 3 , was reported by Stefan et al to promote M polymerization at room temperature. [55] High cis-1,4 selectivity (� 95 %), M n = 13-48.5 kg mol À 1 , and relatively narrow Ð (1.8) were detected. Kinetics experiments demonstrated pseudo-living character of polymerization, confirmed by the successful synthesis, through sequential monomer addition, of block copolymer poly(M-b-I) (M n = 15.5 kg mol À 1 , Ð = 3.1).…”
Section: Group 3 and Rare-earth Metalsmentioning
confidence: 96%
“…In addition, the system had the ability to produce poly(myrcene‐ b‐ isoprene) and poly(myrcene‐ b‐ methyl methacrylate) block copolymers by adding monomers in sequence. Later on, the same group [29] reported that halide‐free neodymium diethyl phosphate complex combined with TIBA promoted the polymerization of Myr to afford polymers with relatively narrow molecular weight distribution ( M w / M n =1.8), moderate molecular weight ( M n =13000 g/mol) and comparatively high cis ‐1,4 selectivity up to 96% (Figure 5). The system also produced block copolymer poly(myrcene‐ b‐ isoprene), containing the composition of 25 mol% of poly( β ‐myrcene) sequence and 75 mol% of poly(isoprene) sequence.…”
Section: Bio‐based Linear Terpenes As Conjugated Dienes For Rare‐eart...mentioning
confidence: 99%
“… In combination of TIBA, neodymium‐based binary catalytic system was used to polymerize Myr. Reproduced with permission [29] . Copyright 2019, The Royal Society of Chemistry.…”
Section: Bio‐based Linear Terpenes As Conjugated Dienes For Rare‐eart...mentioning
confidence: 99%
“…This type of catalyst is highly active and leads to stereoregular polymers with high content of the 1,4- cis microstructure, which is needed for adequate elasticity, high fatigue and crack resistance, and low heat buildup in synthetic rubber. Vulcanized products obtain better mechanical properties (300% modulus, tensile strength, and elongation at breakage) with the content of the 1,4- cis microstructure [ 20 ]. The vulcanization of PM and PF was compared with PB and PI, using the same vulcanization process parameters and with/without carbon black, to elucidate the influence of the chemical structure on the crosslinking network and mechanical properties compared to conventional petroleum-based rubbers.…”
Section: Introductionmentioning
confidence: 99%